Spatiotemporal dynamics and prevention strategies of cervical cancer incidence in Addis Ababa, Ethiopia: an ecological study - Mathewos Assefa; Eva Johanna Kantelhardt; Teferi Gedif Fenta; Tariku Shimels (BMJ Open)
Objective This study analysed the spatial and temporal patterns of cervical cancer incidence in Addis Ababa from 2012 to 2021.Design An ecological study was conducted from 1 September to 30 November 2023 to examine the spatiotemporal trends of cervical cancer incidence.Setting The research was conducted in Addis Ababa, the capital city of Ethiopia.Participants Included were all patients with clinically and/or histopathologically confirmed diagnoses of cervical cancer.Data analysis The study employed advanced analytical tools including R programming, Quantum Geographic Information System V.3.36.0, GeoDa V.1.2.2 and System for Automated Geoscientific Analyses GIS V.9.3.2. Techniques such as Bayesian empirical testing with a block weighting matrix for hotspot identification, Global Moran’s I for spatial autocorrelation, nearest neighbour imputation and universal Kriging interpolation were used to manage data gaps. Joinpoint trend analysis and direct age-standardised incidence rate (ASIR) using the Segi’s World standard population was applied to compare trends across subcities. A statistical significance threshold was set at p<0.05.Results Between 2012 and 2021, a total of 2435 new cervical cancer cases were recorded in the Addis Ababa City Population-based Cancer Registry, with significant spatial clustering observed in Nifas Silk Lafto, Bole, Kirkos as well as parts of Gulele and Yeka sub cities (z score>1.96) in 2018. The citywide age-standardised incidence rate varied from 19 to 26 cases per 100 000 women-years during 2013 and 2016, respectively. Subcity trends varied significantly, with increases and decreases noted in Akaki Kality and Kolfe Keraniyo over different periods while Bole subcity showed modest increase at 4.2% APC (95% CI: 0.6% to 7.9%; p=0.026).Conclusion The study highlights substantial fluctuations in ASIR and significant geographic disparities in cervical cancer throughout Addis Ababa. To address these challenges, the implementation of school-based human papillomavirus vaccination programmes, alongside targeted interventions, active campaigns and sustained surveillance, is critical. These strategies are essential to effectively reduce the cervical cancer burden and improve health outcomes in the community.